A new spotted Chiloschista (Orchidaceae: Aeridinae) from Bhutan - Gyeltshen, Choki (Universidad de Costa Rica, 2019)
A new species of Chiloschista from a restricted area in Bhutan is described and illustrated. It is compared with C. parishii from Myanmar and Thailand, which has similarly colored flowers and from which it differs by the larger flowers, 15–18 mm versus 8–10 mm, and the lack of a glandular and pubescent, erect and curved callus lobe inside the lip, which is generally seen in other similarly colored species of this genus.